Polyelectrolyte Complexation Approach to Devise PEDOT:PSS-Based Moldable, Self-Healable, and Ultra-Stretchable Solid Electrolytes for Underwater Electronics - Anand, Shrinkhala; Tewary, Arpan; Upadhyay, Chandan; Sinha, Akhoury Sudhir Kumar; Ojha, Umaprasana (ACS applied electronic materials, 2024)
PEDOT:PSS-based systems possessing effective optoelectronic behavior are promising for metal particle-free flexible electronics applications. However, these systems currently suffer from low stretchability, mechanical resilience, and performance in aqueous media. In this article, polyelectrolyte complexation between polyacryloyl hydrazide triflate (PAHT) and polystyrenesulfonate (PSS) is utilized to devise conducting ink with tunable viscosity at high PEDOT loading for fabricating stretchable, self-healable, and conductive solid electrolytes for flexible electronics applications. The possible ionic linkages (CONHNH3 +---SO3̅ and SO3̅---CS+) between the polymeric segments enabled film integrity in various organic and aqueous media and imparted effective tensile strength (0.10 MPa) and stretchability (∼1120%), while maintaining effective ionic conductivity (0.18 S/cm). The film displayed an effective ΔR/R 0 value of ∼26.2 at 600% stretching. As a proof of concept, the ability of these solid electrolytes toward strain-sensing application was studied. The system was able to display repeatable change in ΔR/R 0 values in response to various bodily movements under submersible conditions and adequate Gauge factor values of 4.4 and 0.20 under environmental and underwater conditions supporting its viability toward strain-sensing applications.